2006
DOI: 10.1111/j.1478-3231.2006.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral treatment withdrawal in viremic HCV‐positive liver transplant patients: impact on viral loads, allograft function and morphology

Abstract: Our study suggests that antiviral treatment withdrawal carries the risk of severe disease progression in persistently viremic HCV-positive liver transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…In cases of hepatitis B, high serum levels of hepatitis B virus DNA are usually found, and several reports have shown an accumulation of large amounts of hepatitis B virus antigens in hepatocytes. Recently, reports of FCH have been increasing in cases of hepatitis C after LTx [13][14][15]20]. In recurrent hepatitis C after LTx, several researchers have indicated that FCH is caused by a direct cytopathic effect of HCV associated with a high level of HCV replication [9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In cases of hepatitis B, high serum levels of hepatitis B virus DNA are usually found, and several reports have shown an accumulation of large amounts of hepatitis B virus antigens in hepatocytes. Recently, reports of FCH have been increasing in cases of hepatitis C after LTx [13][14][15]20]. In recurrent hepatitis C after LTx, several researchers have indicated that FCH is caused by a direct cytopathic effect of HCV associated with a high level of HCV replication [9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
“…Antiviral therapy with IFN, with or without RBV, has been used in these patients. A few cases have reported successful results, but the prognosis of FCH is generally poor [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…Due to IFN-associated side effects and RBV-induced anemia, antiviral treatment of HCV infection after LT is challenging. Treatment-associated rejection episodes and a flare of liver disease may have resulted in graft failure and ultimately in patient death 12,21,22. With the approval of DAAs, standard of care has changed to a combination therapy with DAAs, in the beginning in combination with PEG-IFN and RBV 23,24.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, although HCV reactivation following immunosuppressive therapy is rare, fibrosing cholestatic hepatitis C (FCH) occurs in HCV positive liver transplant recipients with immunosuppressive therapy . Whether immunosuppressive therapy leads to HCV reactivation in patients with cancer in whom the infection has cleared either spontaneously or secondary to therapy is uncertain.…”
Section: Pathophysiology Of Reactivation Of Hbv and Hcv Infectionmentioning
confidence: 99%